eIF3a Destabilization and TDP-43 Alter Dynamics of Heat-Induced Stress Granules - Malcova, Ivana; Senohrabkova, Lenka; Novakova, Lenka; Hasek, Jiri (International journal of molecular sciences, 2021)
Stress granules (SGs) are membrane-less assemblies arising upon various stresses in eukaryotic cells. They sequester mRNAs and proteins from stressful conditions and modulate gene expression to enable cells to resume translation and growth after stress relief. SGs containing the translation initiation factor eIF3a/Rpg1 arise in yeast cells upon robust heat shock (HS) at 46 °C only. We demonstrate that the destabilization of Rpg1 within the PCI domain in the Rpg1-3 variant leads to SGs assembly already at moderate HS at 42 °C. These are bona fide SGs arising upon translation arrest containing mRNAs, which are components of the translation machinery, and associating with P-bodies. HS SGs associate with endoplasmatic reticulum and mitochondria and their contact sites ERMES. Although Rpg1-3-labeled SGs arise at a lower temperature, their disassembly is delayed after HS at 46 °C. Remarkably, the delayed disassembly of HS SGs after the robust HS is reversed by TDP-43, which is a human protein connected with amyotrophic lateral sclerosis. TDP-43 colocalizes with HS SGs in yeast cells and facilitates cell regrowth after the stress relief. Based on our results, we propose yeast HS SGs labeled by Rpg1 and its variants as a novel model system to study functions of TDP-43 in stress granules disassembly.
Keywords: DNA vazebné proteiny; Heat-Shock Response; Saccharomyces cerevisiae Proteins; Mitochondria; stabilita proteinů; eukaryotický iniciační faktor 3; Saccharomyces cerevisiae; Protein Stability; lidé; Endoplasmic Reticulum; messenger RNA; cytoplazmatická granula; mitochondrie; RNA, Messenger; Cytoplasmic Granules; DNA-Binding Proteins; Eukaryotic Initiation Factor-3; reakce na tepelný šok; endoplazmatické retikulum; Saccharomyces cerevisiae - proteiny; Humans